Polycrystal deformation analysis by high energy synchrotron X-ray diffraction on the 112 JEEP beamline at Diamond Light Source - Korsunsky, A; Song, X; Hofmann, F; Abbey, B; Xie, M; Connolley, T; Reinhard, C; Atwood, R; Connor, L; Drakopoulos, M (2010)
Better understanding of the distribution of elastic and plastic strains in deformed polycrystalline, multiphase materials is important for structural engineering. The deformation response depends upon the interaction of grains of different orientations, and the anisotropy associated with each phase. Strain partitioning and tensile-compressive hardening asymmetry arises due to mismatches in modulus and ductility between grains and phases in alloys such as Ti-6Al-4V that displays both strong anisotropy within one phase and significant differences of properties between phases. Simple four-point bent beam samples were studied using the newly available energy-dispersive X-ray diffraction setup at the high energy white-beam synchrotron beamline I12 (JEEP) at Diamond Light Source. Diffraction patterns from the bent polycrystalline Ti6Al4V samples were collected using the new 23-cell "horseshoe" detector and interpreted using Pawley refinement to extract unit cell parameters, thus allowing elastic strain to be determined. The tensile-compressive hardening asymmetry was quantified for the grains oriented with the basal plane perpendicular to the loading direction. Initial evaluation of the performance of the new instrument is reported. © 2011 Elsevier Ltd. All rights reserved.